Resting-state functional connectivity changes within the default mode network and the salience network after antipsychotic treatment in early-phase schizophrenia - Wang Y (Dove Medical Press, 2017)
Yingchan Wang,1 Weijun Tang,2 Xiaoduo Fan,3 Jianye Zhang,1 Daoying Geng,2 Kaida Jiang,1 Dianming Zhu,1 Zhenhua Song,1 Zeping Xiao,1 Dengtang Liu1 1First-Episode Schizophrenia and Early Psychosis Program, Division of Psychotic Disorders, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, 2Department of Radiology, Huashan Hospital, Fu Dan University, Shanghai, People’s Republic of China; 3Psychotic Disorders Program, UMass Memorial Medical Center, UMass Medical School, Worcester, MA, USA Objective: Abnormal resting-state functional connectivity (FC), particularly in the default mode network (DMN) and the salience network (SN), has been reported in schizophrenia, but little is known about the effects of antipsychotics on these networks. The purpose of this study was to examine the effects of atypical antipsychotics on DMN and SN and the relationship between these effects and symptom improvement in patients with schizophrenia.Methods: This was a prospective study of 33 patients diagnosed with schizophrenia and treated with antipsychotics at Shanghai Mental Health Center. Thirty-three healthy controls matched for age and gender were recruited. All subjects underwent functional magnetic resonance imaging (fMRI). Healthy controls were scanned only once; patients were scanned before and after 6–8 weeks of treatment.Results: In the DMN, the patients exhibited increased FC after treatment in the right superior temporal gyrus, right medial frontal gyrus, and left superior frontal gyrus and decreased FC in the right posterior cingulate/precuneus (P<0.005). In the SN, the patients exhibited decreased FC in the right cerebellum anterior lobe and left insula (P<0.005). The FC in the right posterior cingulate/precuneus in the DMN negatively correlated with the difference between the Clinical Global Impression (CGI) score pre/post-treatment (r=–0.564, P=0.023) and negative trends with the difference in the Positive and Negative Syndrome Scale (PANSS) total score pre/post-treatment (r=–0.475, P=0.063) and the difference in PANSS-positive symptom scores (r=–0.481, P=0.060).Conclusion: These findings suggest that atypical antipsychotics could regulate the FC of certain key brain regions within the DMN in early-phase schizophrenia, which might be related to symptom improvement. However, the effects of atypical antipsychotics on SN are less clear. Keywords: schizophrenia, fMRI, default network, salience network, antipsychotics